PENGARUH METODE GUIDED READING BERBANTUAN MEDIA FLIPBOOK TERHADAP KETERAMPILAN MEMBACA SISWA KELAS III SD - Sri Mulyani; Noviati; Rury Rizhardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of the Guided Reading method assisted by Flipbook media on the reading skills of third-grade students at SD Negeri 58 Palembang. This study employed a quantitative approach with an experimental design involving an experimental group and a control group. Data were collected through tests and documentation. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing through a t-test.The results showed that the mean pretest score of the experimental class increased from 66.46 to 82.50 in the posttest, while the mean pretest score of the control class increased from 57.61 to 65.00. The homogeneity test showed a significance value of 0.693 > 0.05, indicating that the data were homogeneous. The hypothesis test revealed a significance value (Sig. 2-tailed) of 0.000 < 0.05 with a t-value of 6.518. Therefore, H₀ was rejected and Hₐ was accepted. It can be concluded that the Guided Reading method assisted by Flipbook media had a significant effect on the reading skills of third-grade students at SD Negeri 58 Palembang.